Prognostic impact of extranodal extension in stage 1B gastric carcinomas. (June 2018) - Lee, In-Seob; Kang, Hyo Jeong; Park, Young-Soo; Ryu, Min-Hee; Yook, Jeong-Hwan; Kang, Yoon-Koo; Kim, Byung-Sik
Abstract: Background: In addition to the TNM stage, an additional prognostic factor is needed to assess the prognosis of gastric cancer. Moreover, there is no consensus on high-risk group of recurrence and adjuvant strategy in stage 1B gastric cancers. We aimed to investigate the prognostic significance of extranodal extension (ENE) in stage 1B gastric carcinomas and assess whether ENE can indicate the need for adjuvant treatment. Methods: The clinicopathological characteristics of 1588 patients who underwent curative gastrectomy with more than D1 plus lymphadenectomy for stage 1B gastric cancer from 2003 to 2010 were reviewed. A propensity score matching analysis was performed. Results: Age over 65 years and the presence of ENE were found to be poor prognostic factors for both overall survival (OS) and disease-free survival (DFS). Adjuvant chemotherapy was related to an increased overall survival. The 5 year OS and DFS rates were 88.7% and 86.2%, respectively. When divided into 3 groups (early gastric cancer with ENE [T1N1 ENE(+)], early cancer without ENE [T1N1 ENE(−)], and advanced tumor without nodal metastasis [T2N0]), the OS and DFS rates of the T1N1 ENE(+) group were significantly worse than those of the other groups (5 year OS rate of 72.7% vs. 88.4% vs. 91.9%, respectively, P  < 0.001 and 5 year DFS rate of 67.2% vs. 85.2% vs. 91.5%, respectively, P  < 0.001). Conclusion: ENE is an independent prognostic factor that predicted poor outcomes for stage 1B gastric cancers and it could be an indicator of the need for adjuvant treatment. Highlights: Extranodal extension of a metastatic lymph node is an independent prognostic factor for stage 1B gastric carcinomas and should be considered as a prognostic marker. Among stage 1B cancers, it might be reasonable to define T1N1 tumors with ENE as a high-risk group for recurrence and adjuvant treatment could be considered. Detailed pathological examinations to evaluate the presence of ENE are needed.